Down syndrome and its screening: knowledge, attitude and practice among pregnant women in Patan Hospital - Gurung, Padma; Baaniya, Jeena; Malla, Sameer (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Down syndrome (DS) is the most common cause of intellectual disability among live born children which can be detected prenatally. This study aims to assess the knowledge attitude and practice of pregnant women about Down syndrome and its available prenatal diagnosis.Method: A study was conducted in Department of Obstetrics and Gynecology of Patan Academy of Health Sciences in 2021.All pregnant ladies who attended the antenatal clinic received a self-administered validated questionnaire to determine their knowledge of Down syndrome, its screening test and willingness to do prenatal testing.Result: Majority of the participants (88%) belonged to age group of 18 to 35 years.59% were primigravidas. Almost 90% were Hindus and 55% had graduate level education. More than half of the participants had poor knowledge of DS and 60 % had no idea regarding the screening tests. However, more than half (56%) of them were willing to undergo screening for DS. One fifth of the women did not want to continue the pregnancy if baby had DS. Higher income is significantly associated with good knowledge in both domain (knowledge about DS, and knowledge about its screening). Illiterates are found to have better knowledge than educated group which seems a bit contradictory, but this might have been due to our smaller sample size.Conclusion: There is a significant gap between women’s knowledge and their attitudes and practice, which has to be addressed with local and national policies and protocols. Informed decision making should be the norm after empowering pregnant women with knowledge.